Implementation of the cooperative learning model team assisted individualization (TAI) in indonesian language lectures - Anastasia Baan (International Journal of Educational Administration, Management, and Leadership, 2023)
This study aims to determine the increase in semester 1 student learning outcomes of the UKI Toraja Management study program in the Indonesian language course through the application of the Team Assisted Individualization (TAI) Cooperative Learning Model. The sample of this research is 25 students. Data collection techniques using observation and learning achievement tests. Data were analyzed using descriptive statistical techniques to describe the conditions of each variable. The results showed that the ability of lecturers to manage learning with an average score of 4.57 was in the very good category, student activity during the learning process was classified as active with an average percentage of 74.5% which was in the active category, and student learning outcomes after being taught using the Team Assisted Individualization (TAI) cooperative learning model is classified as high with an average of 80.35. This shows that applying the Team Assisted Individualization (TAI) cooperative learning model can improve student learning outcomes in semester 1 of the UKI Toraja management study program in the Indonesian Language Course.